A BRITISH DOCUMENT ON THE DIPLOMATIC LEGATIONS IN BULGARIA IMMEDIATELY BEFORE THE OUTBREAK OF THE BALKAN WARS (Philological Studies, 2025)
The task of diplomacy in every state is to guide and regulate its relations with other international actors, primarily through peaceful means, communication, and negotiation. At the same time, one of its key functions is to inform and analyse — essentially, to collect information from or about other countries, analyse it, and submit it to the Ministry of Foreign Affairs. This very function of diplomacy is the focus of the document presented in this paper. This confidential report, dated January 1912, was sent by H. O. Bax-Ironside, a diplomatic representative of the United Kingdom holding the rank of Envoy Extraordinary and Minister Plenipotentiary in Bulgaria, to the British Foreign Secretary, Edward Grey. It contains an analysis of the diplomatic representatives — primarily of the Great Powers and Balkan states — stationed in the Bulgarian capital who were serving in that role during 1911 (namely, the representatives of France, Italy, Greece, Germany, Russia, Serbia, Austria-Hungary, Turkey, and Romania).The detailed analysis presented in this document clearly demonstrates that Bax-Ironside was an experienced diplomat who conducted a remarkably precise psycho-physical evaluation of his colleagues, as well as an assessment of their political and diplomatic capabilities. This is especially important given that psycho-physical analysis plays a key role in understanding the behaviour, intentions, and decisions of foreign states and their leaders, ministers, diplomats, and consuls. Furthermore, such analysis serves as a tool for forecasting reactions and adjusting diplomatic strategies accordingly. In this context, the British diplomat analyses his colleagues’ thought processes, communication styles, values, traumas, ambitions, and their responses in crisis situations, under pressure, or during negotiations.
Keywords: confidential British diplomatic report, H. O. Bax-Ironside, heads of foreign diplomatic missions in Sofia, psycho-physical analysis, political and diplomatic analysis, national interests